2022
DOI: 10.1093/jncics/pkac082
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends in the cause of death for patients with endometrial cancer

Abstract: Background Racial disparities in endometrial cancer have been reported in the United States, but trends and the underlying causes are not well understood. We aimed to examine the trends and contributing factors in racial disparities for causes of death among endometrial cancer patients. Method In this population-based cohort study, we identified 139 473 women diagnosed with first, primary endometrial cancer between 1992 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The results showed a higher prevalence of serous EC (58% vs. 36%) and carcinosarcoma (25% vs. 16%), and a lower prevalence of endometrioid EC (17% vs. 48%) in black women [66]. A recent cohort analysis of the US SEER program concluded that EC grade and histological subtype explained 24.4% and 20.1% of the black-white EC mortality disparity, respectively [67]. In a separate analysis of the US National Cancer Database, the histologic subtype was deemed accountable for up to 56.2% of the excess relative risk among black patients with EC [68].…”
Section: Histological Differencesmentioning
confidence: 97%
“…The results showed a higher prevalence of serous EC (58% vs. 36%) and carcinosarcoma (25% vs. 16%), and a lower prevalence of endometrioid EC (17% vs. 48%) in black women [66]. A recent cohort analysis of the US SEER program concluded that EC grade and histological subtype explained 24.4% and 20.1% of the black-white EC mortality disparity, respectively [67]. In a separate analysis of the US National Cancer Database, the histologic subtype was deemed accountable for up to 56.2% of the excess relative risk among black patients with EC [68].…”
Section: Histological Differencesmentioning
confidence: 97%
“…There exists a large racial disparity in endometrial cancer (EC) mortality in the United States, with Black patients exhibiting a 5-year mortality rate approximately double that of White patients with EC . Poorer survival is associated with Black race, even after adjusting for surgery, histology, grade, age, stage at diagnosis, comorbid conditions, access to care, and socioeconomic factors . The Cancer Genome Atlas (TCGA) project identified 4 molecular subgroups of EC: DNA polymerase epsilon ( POLE ) ultra-altered, mismatch repair deficiency, copy-number (CN)–low, and CN-high .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Poorer survival is associated with Black race, even after adjusting for surgery, histology, grade, age, stage at diagnosis, comorbid conditions, access to care, and socioeconomic factors. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 The Cancer Genome Atlas (TCGA) project identified 4 molecular subgroups of EC: DNA polymerase epsilon ( POLE ) ultra-altered, mismatch repair deficiency, copy-number (CN)–low, and CN-high. 15 , 16 More recent studies utilized immunohistochemistry staining for p53, finding that this is a cost-effective surrogate for identification of the CN-high group, which has the poorest prognosis.…”
Section: Introductionmentioning
confidence: 99%